Barrier crossing in small avian migrants: individual tracking reveals prolonged nocturnal flights into the day as a common migratory strategy - Adamík, Peter; Emmenegger, Tamara; Briedis, Martins; Gustafsson, Lars; Henshaw, Ian; Krist, Miloš; Laaksonen, Toni; Liechti, Felix; Procházka, Petr; Salewski, Volker; Hahn, Steffen (Scientific reports, 2016)
Over decades it has been unclear how individual migratory songbirds cross large ecological barriers such as seas or deserts. By deploying light-level geolocators on four songbird species weighing only about 12 g, we found that these otherwise mainly nocturnal migrants seem to regularly extend their nocturnal flights into the day when crossing the Sahara Desert and the Mediterranean Sea. The proportion of the proposed diurnally flying birds gradually declined over the day with similar landing patterns in autumn and spring. The prolonged flights were slightly more frequent in spring than in autumn, suggesting tighter migratory schedules when returning to breeding sites. Often we found several patterns for barrier crossing for the same individual in autumn compared to the spring journey. As only a small proportion of the birds flew strictly during the night and even some individuals might have flown non-stop, we suggest that prolonged endurance flights are not an exception even in small migratory species. We emphasise an individual's ability to perform both diurnal and nocturnal migration when facing the challenge of crossing a large ecological barrier to successfully complete a migratory journey.
Keywords: Středozemní moře; Africa, Northern; geografické informační systémy; Mediterranean Sea; migrace zvířat; zpěvní ptáci; zvířata; severní Afrika; Flight, Animal; Songbirds; Breeding; Animal Migration; let zvířat; Geographic Information Systems; chov; Animals